Cadmium impairs the development of natural killer cells and bidirectionally modifies their capacity for cytotoxicity. (January 2023) - Zhang, Yufan; Zhao, Yifan; Zhai, Yue; He, Jinyi; Tang, Mengke; Liu, Yalin; Yao, Ye; Xue, Peng; He, Miao; Li, Qian; Xu, Yanyi; Qu, Weidong; et al.
Abstract: Cadmium (Cd) is a highly toxic heavy metal in the environment. The aim of this study was to investigate the impact of Cd on natural killer (NK) cells. C57BL/6 mice were treated with 10 ppm Cd via drinking water for 3 months, and the development of NK cells in the bone marrow (BM) and the cytotoxicity of mature NK (mNK) cells in the peripheral immune organs were evaluated thereafter; the impact of Cd on the cytotoxicity of mNK cells from human peripheral blood mononuclear cells (PBMC) was also investigated. Whereas Cd treatment impaired the differentiation of NK progenitors in the BM, Cd treatment activated the JAK3/STAT5 signaling to drive the proliferation of mNK cells and thereby lead to a compensation increase of mNK cells in the peripheral immune organs of mice. Additionally, Cd treatment bidirectionally regulated the cytotoxicity of mouse mNK cells to differential tumor cells, dependent on the levels of Fas expression in the tumor cells; mechanically, Cd treatment activated the JAK3/STAT5 signaling to promote the expression of FasL in mNK cells to increase their cytotoxicity, while Cd treatment reduced the expression of granzyme B in mNK cells to impair their cytotoxicity in the peripheral immune organs of mice. Likewise, in vitro assays indicated that Cd treatment also activated the JAK3/STAT5 signaling to increase the expression of FasL, whereas Cd treatment reduced the expression of granzyme B in human mNK cells. Thus Cd treatment impaired the development of NK cells in the BM and bidirectionally regulated the cytotoxicity of mNK cells in the peripheral immune organs, which may extend our current understanding for the immunotoxicity of Cd. Graphical abstract: Image 1 Highlights: Cd impairs the development of NK cells in the bone marrow. Cd decreases the production of granzyme B to impair the cytotoxicity of mature NK cells. Cd activates the JAK3/STAT5 signaling to promote the proliferation of mature NK cells. Cd activates the JAK3/STAT5 signaling to increase FasL-mediated cytotoxicity of mature NK cells.